The Emigration Conundrum: EU Countries of Origin of Migrants Between Integration and Demarcation - Christof Roos; Max Nagel; Hanna Kieschnick; Kseniia Cherniak (JCMS: Journal of Common Market Studies, 2024)
Abstract Based on an analysis of parliamentary debates and party manifestos from 2000 to 2022 in three EU countries of emigration, this article responds to the following question: How emigration is discussed in the political discourse, by whom and why? The research on Poland, Portugal and Romania reveals that parties of the left and right address the societal impacts of emigration whilst simultaneously acknowledging the appreciation of citizens of EU freedoms. Tackling this conundrum, parties call for domestic demarcation for an issue that is partially European. They advocate for state intervention to improve working and living conditions and express concern for the sustainability of the national community responding to demographic changes. The variation amongst the case countries is evident in the dominance of a rightist framing in Central and Eastern Europe, emphasizing state intervention and concerns for the nation, and a leftist framing in Southern Europe, advocating solely for state intervention into the economy. Differently structured party systems and strength of cleavages explain this variation.
Keywords: 330; Central and Eastern Europe; cleavages; demarcation; emigration; integration; Southern Europe